CLINICAL PRACTICE GUIDELINE: MANAGEMENT OF SINUSITIS (SUBJECT REVIEW OF AMERICAN ACADEMY OF PEDIATRICS) - article editorial (Union of pediatricians of Russia, 2006)
This clinical practice guideline formulates recommendations for health care providers regarding the diagnosis, evaluation, and treatment of children, ages 1 to 21 years, with uncomplicated acute, subacute, and recurrent acute bacterial sinusitis. Three specific issues were considered: 1) evidence for the efficacy of various antibiotics in children; 2) evidence for the efficacy of various ancillary, nonantibiotic regimens; and 3) the diagnostic accuracy and concordance of clinical symptoms, radiography (and other imaging methods), and sinus aspiration.It is recommended that the diagnosis of acute bacterial sinusitis be based on clinical criteria in children ≤6 years of age who present with upper respiratory symptoms that are either persistent or severe. Although controversial, imaging studies may be necessary to confirm a diagnosis of acute bacterial sinusitis in children >6 years of age. Computed tomography scans of the paranasal sinuses should be reserved for children who present with complications of acute bacterial sinusitis or who have very persistent or recurrent infections and are not responsive to medical management.There were only 5 controlled randomized trials and 8 case series on antimicrobial therapy for acute bacterial sinusitis in children. However, these data, plus data derived from the study of adults with acute bacterial sinusitis, support the recommendation that acute bacterial sinusitis be treated with antimicrobial therapy to achieve a more rapid clinical cure. Children with complications or suspected complications of acute bacterial sinusitis should be treated promptly and aggressively with antibiotics and, when appropriate, drainage. Based on controversial and limited data, no recommendations are made about the use of prophylactic antimicrobials, ancillary therapies, or complementary/alternative medicine for prevention and treatment of acute bacterial sinusitis.Key words: sinusitis, treatment, management, children.